On Criteria for Evaluating Social Programs - Jorge Luis García; James J. Heckman (Institute of Labor Economics (IZA), 2022)
This paper examines some recently proposed criteria for evaluation of the net social benefits of social programs.
Keywords: D61; 330; cost-benefit analysis; marginal value of public funds